Component Composition and Antimicrobial Activity of Fractions from the Aerial Part of Common Toadflax (Linaria vulgaris Mill.) - T. V. Bombela; O. A. Krotkova; E. E. Galishevskaya; A. G. Anisimova; T. A. Yagontseva; A. V. Agafontseva; V. V. Novikova; A. K. Whaley; A. O. Ponkratova; V. G. Luzhanin (Разработка и регистрация лекарственных средств)
Introduction. Natural biologically active substances (BAS) are distinguished by different polarity, which determines their physicochemical properties, including solubility. When using solvents of different polarity, it is possible to influence the spectrum of BAS extracted from plants, achieving their division into groups, and further achieving isolation in an individual form. Тhe aerial part of Linaria vulgaris Mill. (common toadflax) contains both lipophilic and hydrophilic substances. The herb L. vulgaris is widely used in folk medicine for treatment of angina, conjunctivitis, dermatomycosis, periodontitis and other diseases. Bacterial factors play an important role in the pathogenesis of these diseases.Aim. To study the effect of solvents of different polarity on the component composition of extracted BAS and to study the antimicrobial activity of fractions from the herb L. vulgaris.Materials and methods. The aerial part of L. vulgaris was collected at the flowering stage – at the beginning of fruiting stage in July 2021 in the Perm region. The fractions were obtained by sequential exhaustive liquid-liquid extraction of an alcoholic extract from the herb L. vulgaris with hexane, dichloromethane, and n-butanol. Detection of BAS was carried out by HPLC and planar chromatography on paper. Antimicrobial activity was studied against Escherichia coli, Staphylococcus aureus and Candida albicans.Results and discussion. Using solvents of different polarity four fractions were obtained from the alcohol extract of L. vulgaris: hexane, dichloromethane, n-butanol and water. These fractions have differences in the composition of BAS. The number of polyphenolic substances in the fractions increases with increasing of solvent polarity: hexane (14), dichloromethane (55), butanol (61). The dichloromethane and n-butanol fractions have a similar composition, represented by polyphenolic compounds and iridoids. The main groups of compounds in these fractions are phenolic acids and flavonoids. Iridoids are found in trace amounts. In the hexane fraction, the smallest number of substances was found, iridoids are completely absent, and phenolic acids were found in trace amounts. The water fraction is characterized by the content of the entire BAS complex. The highest antibacterial activity against Escherichia coli and Staphylococcus aureus was found for the aqueous fraction, while the highest antifungal activity was found for the hexane and dichloromethane fractions.Conclusion. Using solvents of different polarity, fractions containing a diverse set of BAS were obtained from the alcoholic extract of L. vulgaris. Fractions exhibiting different polarities from L. vulgaris have antimicrobial activity against Staphylococcus aureus and Escherichia coli, as well as against pathogenic fungi from the genus Candida.